The Adaptation of the adult ınterpersonal acceptance-rejection scale into Turkish and the examination of its psychometric properties - ERDEN ÇINAR, SEVAL (My University, 2022)
This study aims to adapt the Adult Interpersonal Acceptance Rejection Scale to Turkish culture and examine the validity and reliability of the Turkish version of this scale. 653 university students selected by the convenience sampling method constitute the study sample. The original factor structure of the scale was examined by confirmatory factor analysis. The results revealed that the original factor structure of the Adult Interpersonal Acceptance-Rejection Scale was confirmed in the Turkish sample. The internal consistency of the scale items was associated with the Cronbach's alpha reliability coefficient and was calculated as .908. In addition, Cronbach's alpha values were.915 for the mother acceptance sub-dimension, .909 for best friend acceptance sub-dimension, and .911 for the romantic partner acceptance sub-dimension. Correlation coefficients were calculated between the Adult Interpersonal Acceptance Rejection Scale and the Two-Dimensional Self-Esteem Scale, the Interdependent Happiness Scale, and the Life Satisfaction Scale to prove the validity of the criterion. The results showed that the sub-dimensions of the scales were significantly related. These results show that the Turkish version of the Adult Interpersonal Acceptance Rejection Scale is a valid and reliable measurement tool that can be used for research purposes to determine the levels of interpersonal acceptance and rejection of adult individuals.
Keywords: Adult Interpersonal acceptance-rejection; validity; reliability; confirmatory factor analysis